2013
DOI: 10.1371/journal.pgen.1003782
|View full text |Cite
|
Sign up to set email alerts
|

The Spore Differentiation Pathway in the Enteric Pathogen Clostridium difficile

Abstract: Endosporulation is an ancient bacterial developmental program that culminates with the differentiation of a highly resistant endospore. In the model organism Bacillus subtilis, gene expression in the forespore and in the mother cell, the two cells that participate in endospore development, is governed by cell type-specific RNA polymerase sigma subunits. σF in the forespore, and σE in the mother cell control early stages of development and are replaced, at later stages, by σG and σK, respectively. Starting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
326
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(351 citation statements)
references
References 90 publications
(207 reference statements)
21
326
2
2
Order By: Relevance
“…As expected, the C. difficile sigF mutant was unable to form any heat-resistant spores. TEM image analysis revealed that the sigF disruption mutant had its sporulation blocked at asymmetric division and was unable to progress further in spore morphogenesis, which is similar to the observations of the B. subtilis sigF mutant (25,91,94) (Fig. 5).…”
Section: Sporulation-specific Sigma Factors That Are Activated Downstsupporting
confidence: 80%
See 2 more Smart Citations
“…As expected, the C. difficile sigF mutant was unable to form any heat-resistant spores. TEM image analysis revealed that the sigF disruption mutant had its sporulation blocked at asymmetric division and was unable to progress further in spore morphogenesis, which is similar to the observations of the B. subtilis sigF mutant (25,91,94) (Fig. 5).…”
Section: Sporulation-specific Sigma Factors That Are Activated Downstsupporting
confidence: 80%
“…The sigF gene was also disrupted in the important pathogen C. difficile (generating sigF disruption mutant strain AHCD533) (94). As expected, the C. difficile sigF mutant was unable to form any heat-resistant spores.…”
Section: Sporulation-specific Sigma Factors That Are Activated Downstmentioning
confidence: 60%
See 1 more Smart Citation
“…The mechanism of regulation of all these factors is not known and is currently under study. However, Pereira et al observed that as in B. subtilis, the activity of factors F and G in C. difficile is focused on forespores and that of factors E and K on the mother cell (Figure 2) [23].…”
Section: Persistence Of Sporesmentioning
confidence: 99%
“…En C. perfringens, σ K es producido en células en la fase pre-divisional y se encuentra involucrado en la producción de enterotoxina 105 . En cuanto a C. difficile, un estudio mostró que en relación a los roles de los distintos factores sigma involucrados en esporulación, C. difficile parece ser cercano al organismo modelo, B. subtilis, más que a otras especies del género Clostridium 106 .…”
Section: Esporulación Y Producción De Toxinasunclassified